Golden Anniversary celebrated by Grays (Raton Range Raton, New Mexico, 1981)
Newspaper Article on the 50th Anniversary of Roy and Vivian Gray.
Master list item #: 94
File location is in the Raton File Cabinet
Keywords: Gray, Roy; Gray, Vivian; Coen, Dorothy; Hesalroad, Ruth; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Golden, Colorado